2010
DOI: 10.1590/s1806-66902010000200019
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico e qualidade de sementes de cultivares de feijão-caupi na região do cerrado

Abstract: Desempenho agronômico e qualidade de sementes de cultivares de feijão-caupi na região do cerrado 1 Agronomic performance and quality of seeds of cowpea cultivar in the brazilian "cerrado" region Abstract -The productivities of cowpea are low, depending on the use of low productivity capacity cultivar planted, associated with the use of low-quality seeds. The objective of this work was to evaluate the agronomic characteristics and physiological quality in seed lots of different cultivar of cowpea in the "Cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
30

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 12 publications
4
19
1
30
Order By: Relevance
“…For the latter, similar results were found by Mingotte et al (2013) when they evaluated 17 bean genotypes in a Eutrophic Red Latosol in the region of Jaboticabal in the State of São Paulo and observed a mean value for hundred-grain weight of 24.4 g. These values are higher than those found by Teixeira et al (2010) in cowpea cultivars in the Cerrado region (Catalão, in the state of Goiás), where 17 g were obtained for the cultivar BRS Marataoã and 19 g for the cultivar BRS Guariba. Silva and Neves (2011) found an HGW for the cultivars BRS Marataoã (15 g) and BRS Paraguaçu (16.7 g) similar to that considered as standard, and lower than the weight obtained in this study.…”
Section: Production Componentssupporting
confidence: 87%
“…For the latter, similar results were found by Mingotte et al (2013) when they evaluated 17 bean genotypes in a Eutrophic Red Latosol in the region of Jaboticabal in the State of São Paulo and observed a mean value for hundred-grain weight of 24.4 g. These values are higher than those found by Teixeira et al (2010) in cowpea cultivars in the Cerrado region (Catalão, in the state of Goiás), where 17 g were obtained for the cultivar BRS Marataoã and 19 g for the cultivar BRS Guariba. Silva and Neves (2011) found an HGW for the cultivars BRS Marataoã (15 g) and BRS Paraguaçu (16.7 g) similar to that considered as standard, and lower than the weight obtained in this study.…”
Section: Production Componentssupporting
confidence: 87%
“…The S3 sowing season provided grain yields values higher than those reported by Teixeira et al (2010), Matoso et al (2013) and Matoso (2014) under rainfed conditions, and by Silva and Neves (2011) and Silva et al (2013) with the use of irrigation. These results show that the cowpea has significant productive potential (HALL et al, 2003;ALVES et al, 2009) …”
Section: Source Of Variationmentioning
confidence: 55%
“…This expansion was due to the development of new cultivars with compact and erect characteristics, favoring mechanization (FREIRE FILHO et al, 2011), and responsive to soil fertility, and due to the benefits of rotation with other agricultural species, ensuring a more sustainable crop system (HALL et al, 2003). Teixeira et al (2010) studied cowpea crop in a dry season in Catalão, Goias, Brazil, and observed adaptation of the cultivars BRS-Guariba (grain yield of 2,211 ha -1 ) and /87BR17-Gurguéia (2,196 kg ha -1 ) to the local climatic conditions. Matoso et al (2013) found that the grain yield of the cultivar BRS-Novaera ranged from 779 kg ha -1 (2010) to 1756 kg ha -1 (2009), during the winter crop, in Dourados, Mato Grosso do Sul.…”
Section: Introductionmentioning
confidence: 99%
“…Tabela 1 -Análises conjuntas de variância referentes aos testes de: primeira contagem (1ªcont), germinação (G), condutividade elétrica (CE), envelhecimento acelerado (EA), emergência em campo (EC), produtividade (PROD) e peso de mil sementes (PMS) de 26 genótipos crioulos de feijão * significativo a P < 0,01; ** significativo a P < 0,05; ns não significativo (P > 0,05) Os resultados obtidos nos testes de primeira e segunda contagem possibilitaram observar diferenças entre os genótipos, sugerindo existir variabilidade genética para esse caractere e também que esse caractere sofre influência do ambiente de cultivo conforme o genótipo. Desta maneira, alguns genótipos se destacam para determinado ambiente em particular, devido às suas territorialidades, como já foi observado em outras pesquisas (COELHO et al, 2010;TEIXEIRA et al, 2010 T abela 2 -Percentual de germinação (G), envelhecimento acelerado (EA), emergência em campo (EC), condutividade elétrica (CE), produtividade (PROD) e peso de mil sementes (PMS) de 26 genótipos crioulos de feijão, produzidos em três municípios de Santa Catarina …”
Section: Resultsunclassified